Penerapan Metode Jarimatika Untuk Meningkatkan Keaktifan Dan Hasil Belajar Matematika Kelas Ivsdn 2 Bunjeruk - Shahibul Ardhi; Fitria Apriani; Nunik Amrita Aprilia (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Amin, 2023)
This research is entitled "Application of the jarimatics method to improve the activeness and learning outcomes of grade IV Mathematics learning students at SDN 2 Bunjeruk. This study aims to determine the increase in student activeness and learning outcomes using the jarimatics method in grade IV Mathematics learning students of SDN 2 Bunjeruk. The research method used is a descriptive method with the form of research is classroom action research. The results of the study obtained were the average score in cycle I of 66.4 with students who scored above 70 as many as 13 students and in cycle II of 80.4 with students who scored above 70 as many as 16 students and the results of the analysis of student and teacher activities increased from cycle I to cycle II with the meaning of "there is a positive increase by applying the jarimatics method to the numeracy ability of grade IV students of SDN 2 Bonjeruk District Jonggat Central Lombok District academic year 2022/2023". From the data obtained, it shows that the application of the jarimatics method can improve the activeness and learning outcomes of grade IV students of SDN 2 Bonjeruk, Jonggat District.